Arms transfers, neutrality and Britain's role in the Cold War : Anglo-Swiss relations, 1945-1958 - Wyss, Marco (History of warfare ;, 2013)
Marco Wyss examines the extensive Anglo-Swiss armaments relationship between 1945 and 1958 in light of their bilateral relations, and thereby assesses the role of arms transfers, neutrality and Britain, as well as the two countries' relationship during the Cold War.